Peran Madrasah dalam Implementasi Teori Pembelajaran pada Manajemen Pendidikan Islam - Winona Nur Vardhini; Naili Khusniah Annisatul; Sutrimo Purnomo (JURNAL ILMIAH NUSANTARA, 2026)
Madrasah is an Islamic educational institution that plays an important role in integrating general knowledge and Islamic values within the education system. This study aims to examine the role of madrasahs in the implementation of learning theories within Islamic education management, as well as to explore the development of madrasahs from several aspects, including their historical establishment, curriculum development, and the existence of public and private madrasahs. This research uses a qualitative approach with a library research method by collecting data from various relevant sources such as books, scientific journals, and previous studies. The results of the study indicate that madrasahs have experienced significant development over time in terms of management systems, curriculum, and learning methods. The madrasah curriculum continues to evolve following national education policies while maintaining the integration of religious and general knowledge. In addition, both public and private madrasahs contribute to expanding access to Islamic education in society and improving the quality of education. With proper Islamic education management and the effective application of learning theories, madrasahs are expected to produce students who are knowledgeable, faithful, morally upright, and capable of facing the challenges of modern times.